Balsacone C, a New Antibiotic Targeting Bacterial Cell Membranes, Inhibits Clinical Isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) Without Inducing Resistance - Côté, Héloïse; Pichette, André; Simard, François; Ouellette, Marie-Eve; Ripoll, Lionel; Mihoub, Mouadh; Grimard, Doria; Legault, Jean (Frontiers in Microbiology, 2019)
New options are urgently needed for the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections. Balsacone C is a new dihydrochalcone extracted from Populus balsamifera that has been reported previously as being active against Staphylococcus aureus. Here, we evaluate the antibacterial activity of balsacone C against MRSA. Thirty-five (35) MRSA isolates were obtained from hospitalized patients; these isolates were then characterized for their resistance. Most of these MRSA (>85%) were resistant to penicillin, amoxicillin/clavulanic acid, ciprofloxacin, moxifloxacin, levofloxacin, clindamycin, erythromycin, and cefoxitin as well as being sensitive to linezolid, trimethoprim/sulfomethoxazole, rifampicin, and gentamicin. When tested against all MRSA isolates and various gram-positive bacteria, the antibacterial activity of balsacone C produced a MIC90 of 3.8–10.7 µM. We observed no resistant strains of MRSA (against balsacone C) even after 30 passages. Microscopy fluorescence showed that bacteria cell membrane integrity was compromised by low concentrations of balsacone C. Scanning electron microscopy confirmed balsacone C–provoked changes in the bacterial cell membrane and we find a dose-dependent release of DNA and proteins. This loss of cellular integrity leads to cell death and suggests a low potential for the development of spontaneous resistance.